2018
DOI: 10.1093/cid/ciy073
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone-Driven Thermometer Application for Real-time Population- and Individual-Level Influenza Surveillance

Abstract: Smart thermometers represent a novel source of information for influenza surveillance and forecasting. Thermometer readings capture real-time ILI activity at a population level, and they can also be used to generate improved forecasts. Moreover, the widespread deployment of these smart thermometers may also allow for more rapid and efficient surveillance at the household level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 36 publications
1
58
0
Order By: Relevance
“…For example, Fitbit devices have been used to inform timely and accurate models of population-level influenza trends [12]. Additionally, smart thermometers have provided a novel source of information for influenza surveillance and forecasting [13].…”
Section: Surveillancementioning
confidence: 99%
“…For example, Fitbit devices have been used to inform timely and accurate models of population-level influenza trends [12]. Additionally, smart thermometers have provided a novel source of information for influenza surveillance and forecasting [13].…”
Section: Surveillancementioning
confidence: 99%
“…Temperature readings outside of the range 34°C-43°C were not categorized as fever or non-fever readings. 8 Multiple readings and records from a single user (or device, if user was not specified) for a given week were collapsed into a single reading or record indicating whether a fever or symptom occurred at any point during that week, as defined by the CDC weekending date. Number of temperature readings, fevers, and symptom reports were aggregated by week.…”
Section: Smart Thermometer and Mobile Application Datamentioning
confidence: 99%
“…The potential for participatory surveillance for monitoring ILI has been explored in other settings 4,5,6 and in-the-field thermometers have been used for disease monitoring in school children in China. 7 Previous work has shown that smart thermometer readings from the Kinsa application can improve ILI forecasts using national Centers for Disease Control (CDC) data, 8 and we aim to extend this work for influenza and smaller geographic regions. The data collected from temperature readings and user-provided symptom reports from the Kinsa application may be informative for influenza forecasting efforts.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 study suggested that a smartphone-driven thermometry application correlated well with national infl uenza-like illness activity and improved its forecast in real time and up to 3 weeks in advance. 11…”
Section: Obesity a Risk Factor For Infl Uenzamentioning
confidence: 99%